Empowerment resources, decision-making and gender attitudes: which matter most to livestock keepers in the mixed and livestock-based systems in Ethiopia? - Kinati, Wole; Baker, A. Derek; Temple, Elizabeth C.; Najjar, Dina; Mulema, Annet (BMC, 2023)
Women's empowerment constitutes an important aspect of the development agenda. Although it is highly contextual in nature, empowerment literature so far has focussed on identifying factors associated with empowerment, neglecting the importance of understanding which empowerment resources and agency dimensions are more important for whom and under what contexts. This is important, because we cannot talk of empowerment for those who are not in a disempowered condition or who do not value it. We examine the gender differences in the relative valuations of empowerment resources and decision-making areas across different farming systems, and examine the most valued empowerment resources.